The Impact of Green Investment, Technological Innovation, and Globalization on CO2 Emissions: Evidence From MINT Countries - Li, Shijie; Yu, Yang; Jahanger, Atif; Usman, Muhammad; Ning, Yifan (Frontiers in Environmental Science, 2022)
The Mexico, Indonesia, Nigeria, and Turkey (MINT) countries have practiced significant levels of economic growth over the years. However, these countries have not managed to protect their environmental quality in tandem. Thus, the aggravation of environmental indicators traversing these countries radiates a shadow of uncertainty on their achievement of economic growth sustainability. In this regard, green investment and technological innovations are commonly considered as an effective aspect geared to minimize CO2 emissions, as these increase energy efficiency and involve cleaner production. Thus, this study investigates the effect of green investment, economic growth, technological innovation, non-renewable energy use, and globalization on the carbon dioxide (CO2) emissions in MINT countries from 2000 to 2020. After checking the stationary process, this study applied fully modified ordinary least square and dynamic ordinary least square methods to estimate the long-run elasticity of the mentioned regressors on CO2 emissions. The outcomes show that non-renewable energy and technological innovations significantly increase environmental degradation. In contrast, the globalization process and green investment significantly reduce it in the long run. Moreover, the interaction effect of green investment and globalization significantly overcomes the pressure on the environment. Similarly, the moderation effect of technological innovation and globalization significantly reduces the emission level in the region. Moreover, the U-shaped environmental Kuznets curve hypothesis was observed between economic growth and carbon emission across the MINT countries. Furthermore, the findings of the Dumitrescu and Hurlin’s panel causal test disclose that bidirectional causality exists between green investment, globalization, technological innovations, non-renewable energy, and CO2 emissions. This study also recommends some valuable policy suggestions to governments in general and to policymakers specifically which are aimed to endorse environmental sustainability in the MINT countries.